Family Functioning Affected by Adolescent Idiopathic Scoliosis in China: A Cross-Sectional Study - Huang, Yue; Liu, Fuze; Gao, Dejin; Wang, Hai (Frontiers in Pediatrics, 2022)
Adolescent idiopathic scoliosis(AIS) is a common chronic disease in youths, presenting with spinal deformity. Previous studies reported that the family functioning of family members would be affected after a child is diagnosed with a chronic health condition. But no previous study focused on the relationship between AIS and family function. This study is a cross-sectional study that enrolled 54 AIS families and 92 ordinary families, and evaluated their family function in 7 domains using McMaster family assessment device (FAD). The result shows that AIS family gets a lower score than a healthy family in all 7 subscales except for problem solving subscale. There is no significant difference between the AIS patients (1.90±0.42 2.23±0.32) and their parents (1.92±0.35 2.21±0.29) in all seven subscales (p≥0.05). The scores of the parents were moderately/strongly correlated with those of the AIS patients in all seven subscales (𝛄=0.456 0.696, p<0.05). 20.4% to 87.0% of the families experienced unhealthy family functioning, and affective involvement (57.4%) and behavior control (87.0%) were the unhealthiest subscales with the mean scores above the cut-off. Better education experience of Patients’ mother (p=0.04, Odds ratio [OR]=0.14) was the independent protect factor of unhealthy affective involvement in AIS family. It can be concluded that the AIS family performed better than a healthy family in family functions. Better education experience of Patients’ mother was an independent protect factor of unhealthy affective involvement function.